Kaichuang xin shiqi -Qingzhu Zhonghua renmin gongheguo chengli wushi zhounian (1999)
'Usher in a new epoch -Celebrate the 50th anniversary of the founding of the People's Republic of China'. ISBN 7-80580-537-7/J.500.